Children's Language According to Phonological and Morphological Aspects in Vocal Learning at PAUD Al-Karimah - Natsir, Muhammad; Fazalani, Runi; Maldin, Siska Amelia; Suhartiwi, Suhartiwi; Yanti, Ipri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research is important to determine children's language acquisition and development according to studies of phonology and morphology in Indonesian language learning. The method used in this research is qualitative method with a case study approach. Through this qualitative method, the phonetic system of Edwin Omar Malik Erdogan (2.6 years) and Edward Nazhan Naik Erdogan (4 years), who are students at PAUD Al-Karimah, will be described. These two subjects were used as research samples from ten students to make the findings more accurate regarding learning outcomes and descriptive evidence of early childhood language acquisition at PAUD Al-Karimah. The result of this study was the Acquisition of phonology in their daily lives. Edwin and Edward obtained five vowel sounds Indonesians produced. The vowel sound consists of [a], [i], [u], [e], [o]. So it can be concluded that Edwin and Edward have mastered all vowel sounds, and there are consonant sounds, as many as 19 consonants Indonesian produced by Edwin and Edward. The consonant sounds consist of [b], [c], [d], [g], [h], [j], [l], [m], [n], [p], [s], [t], [w], [y], [G], [S], [ṭ], [?]. The consonant sounds that are not pronounced are [k], [f], [q], [r], [v], [x], [z].